Rectal mucosal plasma cells in inflammatory bowel disease. Issue 6 (June 1983) - Scott, B B; Goodall, A; Stephenson, P; Jenkins, D
Abstract : To achieve optimum staining and reproducible counts of plasma cells in paraffin embedded tissue with the immunoperoxidase technique we have found it essential to obtain a plateau count by titration of antisera for each specimen. This modification was used to study IgA, IgM, IgE, and IgG plasma cells in rectal biopsies from 20 controls, 20 patients with ulcerative proctocolitis, 20 with Crohn's colitis, 20 with non-specific proctitis, 15 with bacterial colitis, and seven with Crohn's disease but no apparent large bowel involvement. Counts were correlated with the characteristic histological features of inflammatory bowel disease. In controls the ratio of the mean counts for IgA, IgM, IgE, and IgG plasma cells was 8:3:3:1. All types of plasma cells were very significantly increased in the patients with ulcerative proctocolitis, Crohn's colitis, and non-specific proctitis and counts correlated with the severity of inflammation. There was no significant difference between the counts in these three groups. All counts tended to be higher in bacterial colitis than in controls, the difference being significant for IgA and IgE. When matched for severity of inflammation there was no significant difference between the counts in bacterial colitis and inflammatory bowel disease. The counts in patients with Crohn's disease but no large bowel involvement were not significantly different from controls. These results suggest that changes in plasma cell counts in inflammatory bowel disease are a non-specific response to mucosal damage, possible by a luminal irritant, and do not differentiate the type of inflammatory bowel disease.